Penggunaan Majas Dalam Lirik Lagu “Remaja” Karya HIVI - Meti Amarila Lestari; Putri Annisa Nurfitriani; Septa Adistya Kusnandar Syahputri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Songs are included in poetic literary works that continue to develop over time. The words used in it are interesting things that must be researched because of the use of beautiful and different language in general. Like one of the songs that is popular among young people, the song